How the experiences of implementation support recipients contribute to implementation outcomes - Allison J. Metz; Todd M. Jensen; Jenny L. Afkinich; Mackensie E. Disbennett; Amanda B. Farley (Frontiers in Health Services, 2024)
IntroductionThere is a growing body of literature on the activities and competencies of implementation support practitioners (ISPs) and the outcomes of engaging ISPs to support implementation efforts. However, there remains limited knowledge about the experiences of implementation support recipients who engage with ISPs and how these experiences shape the trajectory of implementation and contribute to implementation outcomes. This study aimed to extend the research on ISPs by describing the experiences of professionals who received implementation support and inform our understanding of the mechanisms by which ISPs produce behavior change and contribute to implementation outcomes.MethodsThirteen individuals with roles in supporting implementation efforts at a private foundation participated in semi-structured interviews. Data were analyzed using qualitative narrative analysis and episode profile analysis approaches. Iterative diagramming was used to visualize the pathway of experiences of implementation support recipients evidenced by the interview data.ResultsThe majority of recipients described how positive experiences and trusting relationships with ISPs increased acceptance of implementation science throughout the foundation and increased the perception of implementation science as both an appropriate and feasible approach for strengthening the impact of foundation strategies. As perceptions of appropriateness and feasibility increased, recipients of implementation support described increasing knowledge and application of implementation science in their funding engagements and internal foundation strategies. Finally, recipients reported that the application of implementation science across the foundation led to sustained implementation capacity and better outcomes.DiscussionThe experiences of implementation support recipients described in this paper provide a source for further understanding the mechanisms of change for delivering effective implementation support leading to better implementation quality. Insights from these experiences can enhance our understanding for building implementation capacity and the rationales for evolving approaches that emphasize the dynamic, emotional, and highly relational nature of supporting others to use evidence in practice.